Test Signal Selection for Determining the Sound Scattering Coefficient in a Reverberation Chamber - Tadeusz KAMISIŃSKI; Krzysztof BRAWATA; Adam PILCH; Jarosław RUBACHA; Marcin ZASTAWNIK (Archives of Acoustics)
The paper focuses on the problem of test signal selection in determining the sound scattering coefficient in accordance with ISO 17497-1. Research shows that the use of MLS signal is preferred in this procedure. The sine sweep signal, despite its advantages, presents certain limitations if the sample is moving during measurement. An attempt has been made to develop a method that allows for minimization of error, demonstrating the dependence of the obtained values of the sound scattering coefficient on the rotational speed of the turntable and type of test signal. Conditions for the application of the sine sweep signals in continuous and discrete measurements were defined.